Ultra-Wideband Communication System with High Data Rate - Immoreev, I.J.; Sudakov, A.A. (Радиофизика и радиоастрономия, 2002)
The ultra-wideband communication system with high data rate is considered. Information in the system is transmitted by train of short pulses, which have duration about 1.0 ns. The hardware realization of the system is offered. The simulation of the system operation is presented. Рассматривается сверхширокополосная система связи с высокой скоростью передачи данных. Информация в системе передается посредством серии коротких импульсов, длительность которых около 1 нс. Предлагается аппаратная реализация системы. Представлена модель функционирования системы. Розглянуто надширокосмугову систему зв’язку з великою швидкістю передавання даних. Інформація в системі передається за допомогою серії коротких імпульсів, тривалість яких біля 1 нс. Пропонується апаратна реалізація системи. Представлено модель функціонування системи.